The effect of glutamate on ghrelin release in mice. (23rd January 2017) - Chacrabati, Rakhi; Gong, Zhi; Ikenoya, Chika; Kondo, Daisuke; Zigman, Jeffrey M.; Sakai, Takafumi; Sakata, Ichiro
Abstract: Ghrelin is abundantly produced in the stomach. Here, we found that glutamate decreased ghrelin expression and release in ghrelin‐producing cells, and decreased levels of food intake and plasma acyl‐ghrelin in mice. Treatment with siRNA of G protein‐coupled receptor, family C, group 5, member B (GPRC5B) in ghrelin‐producing cell lines completely blocked the effect of glutamate‐induced ghrelin suppression. In addition, glutamate inhibited ghrelin release via the extracellular signal‐regulated kinase (ERK) activity pathway, and stimulated CREB2 mRNA expression in ghrelin‐producing cell lines. These results suggest that glutamate inhibits ghrelin release via ERK‐CREB2 pathway. These results suggest that the GPRC5B‐ERK‐CREB2 pathway is involved in the inhibition of ghrelin expression and secretion in ghrelin cells.